DEVELOPMENT OF SUFI DOKTRINE IN THE RELIGIOUS AND PHILOSOPHICAL VIEVS OF ABU HAMID AL-GHAZALI AND IBN AL-ARABI (Scientific journal of the Fergana State University, 2023)
In the article, the religious-philosophical and mystical views of Abu Hamid al-Ghazali and Ibn al-Arabi are essentially religious-mystical and moral-philosophical teachings. Ontological questions about God, the Universe and Man are the main problem and idea in the teachings of Imam al-Ghazali and Ibn al-Arabi. took for their philosophical essence the fact that they developed irrationalistic principles along with rational thinking in the understanding of God and His creations.